(untitled) (Global Journal of Medical Research, 2018)
The immunity and protective capability produced by vaccines can vary remarkably according to the kinds of adjuvant being used. Through this work three formulae of the inactivated trivalent FMD vaccine (O pan Asia, A Iran O5 , and SAT2 / EGY/2012) were prepared using different adjuvants including Emulsigen ® -D; Montanid ISA 206 and Emulsigen ® -D (ED) with aluminum hydroxide gel (ALOH). All of these vaccine formulae were found to be free from foreign contaminants and safe. Also, each vaccine formula was injected in a separate sheep group and serum samples were collected along 38-week post-vaccination for tracing of antibodies against FMDV serotypes by serum neutralization test (SNT) and enzyme-linked immune sorbent assay (ELISA).